State Agency Programs for Bobwhite Quail Management on Private Lands - Robert T. Dumke (National Quail Symposium Proceedings, 2017)
(Invited Paper) State programs to protect and improve wildlife habitat on private lands have characteristically provided indirect incentives including plant materials, signs, technical advice, and trespass control, Bobwhite quail have, no doubt, benefited from these programs although Wisconsin had the only project which specifically featured the species. The high level of participation in the Wisconsin endeavor suggested that certain cohorts of the private sector are willing to work cooperatively with land managers to improve wildlife resources. An interagency, comprehensive land management approach is needed. Wildlife habitat can be benefited by the improved management of soil, water, plant, and animal resources, Specific programs for quail habitat management on private lands will likely work best under a user-pays concept involving hunting recreation.